1692 No Longer Unknown: A Systematic Review & Meta-Analysis of The Effectiveness of Trans-Oral Surgical Techniques in Identifying Head and Neck Primary Cancer in Carcinoma Unknown Primary. (12th October 2021) - Gao, C; Al-Lami, A; Al-Zuhir, N; Simo, R; Arora, A; Jeannon, J P
Abstract: Aim: The use of transoral robotic surgery (TORS), transoral laser microsurgery (TLM) and more recently reported transoral endoscopic electrocautery (TOEC) in the identification of the primary cancer in CUP patients has gained popularity. This systematic review aims to assess the effectiveness of TORS, TLM and TOEC. Method: A systematic review and meta-analysis using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) reporting methodology was carried out to assess the effectiveness of the three trans-oral surgical techniques. EMBASE, MEDLINE and CINAHL databases were searched from inception to September 2020. Primary outcome measure was detection rates of primary cancer of the different techniques. Secondary outcome measures were complications and length of hospital stay. Results: 289 studies were identified of which 30 met the inclusion criteria (28 case series and 2 case reports). The overall combined primary identification rate was 72.3% (567 /777 patients). The primary identification rates were 49.7% and 34.2% in lingual (n = 273) and palatine tonsillectomy (n = 118) respectively. The primary cancer identification rates by surgical techniques are: TORS was 60% (CI 0.49, 0.70), TLM was 80% (CI 0.58, 1.01), TOEC was 41% (CI 0.05, 0.76). The commonest complication was haemorrhage (5.3%). Conclusions: This is the largest systematic review in the subject and incorporates the more recently published surgical technique of TOEC. Lingual tonsillectomy is an effective procedure in CUP work up. Further larger, multi-centre, prospective studies of PET CT negative CUP patients is needed to draw conclusive results